Method for improving film thickness uniformity of lithium tantalate bonding sheet
By fine thinning and polishing the lithium tantalate bonding sheet, combined with partition pressurization and real-time film thickness measurement, the problem of poor film thickness uniformity of lithium tantalate bonding sheet is solved, and efficient and uniform control of film thickness is achieved.
Patent Information
- Application Number
- CN202510405863.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The existing lithium tantalate bonded sheet films are prone to bending and deformation and poor fragmentation during processing, and the film thickness is uneven after polishing, which is difficult to correct, resulting in poor film thickness uniformity.
By performing crude thinning and fine thinning processing on lithium tantalate bonded sheets, combining partition pressurization and real-time film thickness measurement, fitting the polishing rate model, and adjusting the pressurized formula for polishing to ensure film thickness uniformity.
The uniformity of the film thickness of the lithium tantalate bonded sheet is significantly improved, and the extreme thickness difference in the film thickness is reduced, ensuring the consistency of the film thickness during batch processing, and avoiding the problem of uneven film thickness after polishing.
Smart Images

Figure CN119897756A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor materials, and in particular relates to a method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet. Background Art
[0002] With the rapid development of the mobile communication industry, filters, as an important part of the radio frequency system, are gradually developing towards high frequency, composite, miniaturization and integration. Traditional surface acoustic wave (SAW) filters have problems such as low frequency and poor temperature stability, and cannot meet the performance requirements of the new generation of devices; while the wafer bonding process can achieve new structures, efficient and low-cost manufacturing and heterogeneous integration of materials.
[0003] Lithium tantalate (LiTaO3) crystals have excellent piezoelectric, acousto-optic, ferroelectric, and pyroelectric effects, and have advantages such as large piezoelectric coefficient, small frequency temperature coefficient, and high electromechanical coupling coefficient. They are basic functional materials in the fields of surface acoustic wave devices, optical communications, lasers, and optoelectronics. In order to improve the performance of surface acoustic wave filters, it is necessary to use bonding technology to combine lithium tantalate wafers with other material wafers to meet the requirements of low insertion loss, high bandwidth, and good thermal stability of surface acoustic wave filters. However, the existing lithium tantalate bonding sheet thin film and thick film products need to be machined to thin and polish the lithium tantalate bonding sheet. During the processing of large-sized lithium tantalate bonding sheets, as the film layer becomes thinner, the film is very likely to bend and deform, or even produce fragments; during the polishing process, the temperature, internal stress during the processing, and the uneven distribution of the polishing liquid may cause uneven film thickness, and the polishing film thickness is not easy to correct. Therefore, it is urgent to develop a method to improve the uniformity of the film thickness of lithium tantalate bonding sheets.
[0004] The invention patent with publication number CN118081603A discloses a bonding wafer polishing method, which provides a matching carrier, places the bonding wafer in the carrier to perform a double-sided polishing process, and controls the polishing removal amount of the top silicon layer, improves the thickness uniformity of the top silicon layer after double-sided polishing, and reduces the wear of the carrier. However, this method is only applicable to the polishing of silicon-silicon bonding wafers. For lithium tantalate-silicon bonding wafers, due to the different hardness of the two, under double-sided polishing conditions, even if the carrier is suitable, the removal rate of the lithium tantalate surface and the silicon surface is very different, and the thickness of the lithium tantalate film cannot be evenly controlled.
[0005] The invention patent with publication number CN104779143A discloses a thin film arranged on a substrate and a preparation method thereof. The invention is to first prepare a thin film layer on a substrate of the same material, with a sacrificial layer between the thin film layer and the substrate of the same material, and then bond the thin film layer to the target substrate, remove the sacrificial layer, separate the thin film and the substrate of the same material, or remove the substrate of the same material by grinding or corrosion, and then remove the sacrificial layer, and finally obtain the thin film layer on the target substrate. Its advantage is that it is not limited by the difference in thermal expansion coefficient between the original substrate and the target substrate, and the overall transfer of the thin film between the original substrate and the target substrate can be achieved. The defect density of the formed thin film layer is low and the thickness is uniform, and the thickness reaches the nanometer level. However, this method is only applicable to thin film products. When the film thickness exceeds 1μm or even reaches 30μm, the use of ion implantation technology cannot efficiently prepare the film, and too long an implantation time will produce corresponding defects and reduce the yield.
[0006] Therefore, the prior art lacks a method for improving the uniformity of the film thickness of lithium tantalate bonding sheets that is efficient, not prone to fragmentation, and has fewer film defects. Summary of the invention
[0007] The invention provides a method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet to solve the deficiencies of the prior art. The method has a stable processing process and solves the problem of poor uniformity of the film thickness during batch preparation of the existing lithium tantalate bonding sheet thin films.
[0008] The invention discloses a method for improving the uniformity of film thickness of a lithium tantalate bonding sheet, comprising the following steps:
[0009] Step a: thinning the lithium tantalate bonding sheet, including:
[0010] The lithium tantalate bonding sheet is subjected to a rough thinning process in sequence to reduce the thickness by a first removal amount; and
[0011] Performing fine thinning processing on the lithium tantalate bonding sheet to reduce the second removal amount;
[0012] Step b: pressurizing the bonded sheet to be polished according to the film thickness distribution of the lithium tantalate bonded sheet after thinning, fitting the polishing rate model according to the film thickness measured in real time, and adjusting the pressurizing formula for polishing.
[0013] In the above step a, in the rough thinning process, the first removal amount needs to be greater than 50 μm, the grinding wheel used is 3000-4000 mesh, the grinding wheel speed is 1500-2000 rpm, the carrier speed is 100-500 rpm, the rough thinning slow lift time is 5-10 s, and the slow lift rate is 0.5-0.8 μm / s; wherein, the grinding wheel used for the rough thinning process is preferably 3000 mesh;
[0014] In the fine thinning process, the second removal amount is 10-15 μm, the grinding wheel used is 8000 mesh, the grinding wheel speed is 1000-1500 rpm, and the stage speed is 100-300 rpm;
[0015] The fine thinning needs to be divided into three steps. The first step is to remove 7~12μm, and the removal rate is 0.3~0.5μm / s; the second step is to remove 2μm, and the removal rate is 0.1~0.3μm / s; the third step is to remove 1μm, and the removal rate is 0.05~0.1μm / s. The slow lifting time of fine thinning is 5~15s, and the slow lifting rate is 0.1~0.5μm / s.
[0016] In the above step a, after the lithium tantalate bonding sheet is subjected to rough and fine thinning processing, the spark time is 5 to 10 seconds, and the spark time is positively correlated with the extreme difference of the film thickness;
[0017] In the above step a, the thinned lithium tantalate bonding sheet is cleaned and dried, the cleaning time is 5 to 10 seconds, and the drying and purging time is 5 to 10 seconds;
[0018] Before polishing the thinned lithium tantalate bonding wafer, use a polishing correction wheel with pure water to dress the polishing pad. The correction wheel speed is 50~100rpm, the correction wheel pressure is 0.5~2psi, and the scanning time is 5~10s.
[0019] In the above step b, the maximum pressure of the wafer is ≤6psi, the maximum pressure of the retaining ring is ≤6psi, the maximum speed of the polishing head is ≤100rpm, and the maximum speed of the polishing plate is ≤100rpm, wherein the speed of the polishing head must be greater than the speed of the polishing plate, and the difference between the two must be within 3~5rpm;
[0020] In the above step b, the polishing head swings left and right with an amplitude of 30 to 50 cm and a swing rate of 5 to 10 cm / min during polishing;
[0021] In the above step b, the lithium tantalate bonding sheet is divided into a circular area and three adjacent concentric annular areas surrounding the circular area in sequence, which are respectively recorded as Zone 4 (Zone4) / Zone 3 (Zone3) / Zone 2 (Zone2) / Zone 1 (Zone1) from the inside to the outside;
[0022] The center of the circle of Zone4 / Zone3 / Zone2 / Zone1 coincides with the center of the circle of the lithium tantalate bonding sheet, the radius of the circular area Zone4 is 20% of the radius of the bonding sheet, the inner and outer radii of the annular area Zone3 are 20% and 60% of the radius of the bonding sheet respectively, the inner and outer radii of the annular area Zone2 are 60% and 90% of the radius of the bonding sheet respectively, and the inner and outer radii of the annular area Zone1 are 90% and 100% of the radius of the bonding sheet respectively;
[0023] The film thickness distribution of Zone4 / Zone3 / Zone2 / Zone1 after thinning is measured by a film thickness meter. The number of measurements by the film thickness meter is greater than 30 and is evenly distributed in each zone. The average film thickness of each zone is calculated based on the film thickness measurement results in each zone.
[0024] In the above step b, the thinned lithium tantalate bonding sheet is polished by applying pressure in different zones and steps according to the film thickness distribution of the thinned bonding sheet;
[0025] The zoned pressurization is usually performed because the outermost annular area of the bonding wafer is in the most contact with the polishing liquid and has the largest polishing removal amount. Zone 1 is used as the reference area, and the set pressure is determined according to the percentage by which the average film thickness of Zone 2 / Zone 3 / Zone 4 is greater than or less than the average film thickness of Zone 1, and pressurization is performed;
[0026] The step-by-step pressurization process increases or decreases the pressure in adjacent steps by no more than 1.5 psi, and in the polishing process, the wafer pressure and the retaining ring pressure can be adjusted to the maximum only after the polishing head speed and the stage speed reach the maximum, so as to avoid the generation of polishing debris;
[0027] In the above step b, the film thickness is measured in real time using a spectral analysis measurement method, the number of measurement points is 400-700 and evenly distributed in each area, the refractive index of lithium tantalate is 2.18, when the processed film thickness is greater than 5μm, the measurement clutter at 2μm needs to be filtered out;
[0028] During batch processing, on the one hand, consumables such as polishing pads, retaining rings, and halogen lamps for film thickness measurement will be consumed as polishing progresses, resulting in differences in the processing environment of different lithium tantalate bonding sheets, and differences in the measurement points of different lithium tantalate bonding sheets. On the other hand, there are problems with the small amount of data and measurement accuracy in the early stage of film thickness measurement, resulting in distortion of measurement data. Using real-time measurement data as polishing downtime data will result in deviations;
[0029] Furthermore, in the above step b, the polishing rate model is fitted at different stages of polishing for downtime thickness compensation. Under the premise of consistent polishing procedures, the polishing pad, retaining ring and halogen lamp for film thickness measurement are divided into use stages with 1000min intervals, and the polishing thickness and polishing time are recorded to calculate the polishing rate every 40s, and the polishing rate curve is fitted;
[0030] The total effective polishing time of the polishing rate model is within 200 seconds. The final stop thickness is calculated based on the model to determine whether it is reasonable and to obtain compensation.
[0031] If the required polishing amount cannot be achieved according to the existing polishing rate model, secondary polishing is required to ensure the consistency of the average film thickness of the lithium tantalate bonding sheet during batch processing;
[0032] The secondary polishing includes flat polishing and zone-by-zone step-by-step pressure polishing.
[0033] First, polish for 200 seconds in a flat polishing manner (i.e., the set pressures in Zone 1, Zone 2, Zone 3, and Zone 4 are equal). Since the wafer surface is a polishing surface during the second polishing, the polishing rate is relatively lower than that of the wafer after thinning. After flat polishing, the remaining polishing amount is polished by step-by-step pressurization at 80% of the rate calculated by the first polishing rate model.
[0034] The polished lithium tantalate bonding wafer is scrubbed for 60 to 120 seconds and dried for 60 to 120 seconds, and then the film thickness is measured.
[0035] The present invention discloses a method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet, which also involves a method for calculating the set pressure of different areas when pressurizing the areas, specifically:
[0036] Taking Zone 1 as the reference zone, the set pressure of the reference zone is determined as the reference pressure P Wafer , according to the percentage of the average film thickness of the remaining areas being greater than or less than the average film thickness of the reference area, the set pressure of the remaining areas is determined. The calculation method of the polishing set pressure of any area in the remaining areas follows formula (1):
[0037] ----(1);
[0038] Among them, P i is the set pressure of any of the remaining areas, D i is the average film thickness of the region, i=2, 3, 4; D1 is the average film thickness of the reference region; P Wafer is the base pressure, α is the coefficient. Wafer and α The value of varies according to the size of the range of the mean film thickness in Zone1 / Zone2 / Zone3 / Zone4, specifically:
[0039] When the range of the mean film thickness is less than 600nm, P Wafer =4.0psi, α =1.0;
[0040] When the range of the mean film thickness is greater than or equal to 600nm and less than 1000nm, P Wafer =3.0psi, α =1.3;
[0041] When the range of the mean film thickness is greater than or equal to 1000nm, P Wafer =3.0psi, α=1.5;
[0042] The calculation result of the set pressure is rounded to one decimal place.
[0043] If the average film thickness in Zone 1 is not the thinnest, that is, among the remaining zones, at least one zone has a set pressure calculation value that is less than the reference pressure P Wafer When the actual set pressure of all zones increases by the same value on top of the original set pressure, the minimum value of the actual set pressure in the remaining zones is equal to the reference pressure P Wafer For example, taking Zone 1 as the reference area, when the range of the mean film thickness is less than 600nm, P Wafer =4.0psi, the calculated values of the set pressures of Zone1 / Zone2 / Zone3 / Zone4 are 4.0 / 3.9 / 3.9 / 4.1psi respectively, then the actual set pressures are 4.1 / 4.0 / 4.0 / 4.2psi;
[0044] If the calculated set pressure exceeds 6 psi, 6 psi will be used as the actual set pressure.
[0045] Preferably, the wafer material bonded to the lithium tantalate wafer is one of sapphire, silicon, silicon carbide and quartz, and the shape and size of the sapphire, silicon, silicon carbide and quartz are consistent with those of the lithium tantalate wafer;
[0046] As a preferred method, the edge of the lithium tantalate bonding sheet needs to be processed with a terrace, the terrace width needs to be 2~3mm, and the terrace angle is 40~50°;
[0047] Preferably, the ambient temperature during polishing is 20-25°C, the relative humidity level is 50±10%, and there is no external vibration or noise;
[0048] Preferably, the thickness of the retaining ring used for polishing is the thickness of the lithium tantalate bonding sheet to be processed minus 50-150 mm.
[0049] In order to improve the uniformity of the film thickness of the lithium tantalate bonding sheet, compared with the prior art, the present invention has the following beneficial effects:
[0050] First, in terms of material control before polishing, the thinning process is optimized by precisely controlling the thinning removal amount to ensure the uniformity of the polishing material of the lithium tantalate bonding wafer; at the same time, the spark time parameters are optimized to control the extreme difference in film thickness, providing a prerequisite for improving polishing uniformity;
[0051] Secondly, through the single-wafer polishing process, a zoned and step-by-step pressurization strategy is used for polishing according to the film thickness distribution within the wafer, which significantly reduces the extreme difference in film thickness within the lithium tantalate bonding wafer, thereby effectively improving the uniformity of film thickness of the single-wafer lithium tantalate bonding wafer;
[0052] Thirdly, the polishing rate of the lithium tantalate bonded wafer at different polishing stages is calculated based on the real-time measured film thickness, which is used to fit the polishing rate model. The model can first be used for real-time measurement of film thickness compensation, and secondly, when the real-time measured film thickness is used as a shutdown condition, if there is still a film thickness deviation, a second polishing can be performed based on the model to correct the film thickness, reducing the film thickness difference between lithium tantalate bonded wafers during batch processing, thereby effectively improving the film thickness uniformity between lithium tantalate bonded wafers during batch polishing. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a processing flow chart of the present invention;
[0054] Figure 2 This is a schematic diagram of the pressure partitioning during the polishing of the lithium tantalate bonding wafer;
[0055] Figure 3 Schematic diagram of film thickness after polishing in Example 1;
[0056] Figure 4 is a scatter plot of the film thickness of Example 2 versus polishing time, showing a reference curve of the film thickness change during polishing;
[0057] Figure 5 Schematic diagram of the film thickness after polishing of Comparative Example 1. DETAILED DESCRIPTION
[0058] The present invention will be further described below in conjunction with the embodiments, but the protection scope of the present invention shall not be limited thereto.
[0059] Example 1
[0060] (1) The lithium tantalate bonding wafer was rough thinned, with a rough thinning removal amount of 200 μm, a grinding wheel speed of 1800 rpm, and a stage speed of 300 rpm; the rough thinning was divided into two steps, the first step of the removal amount was 195 μm, and the removal rate was 1 μm / s; the second step of the removal amount was 5 μm, and the removal rate was 0.5 μm / s; the slow lifting time was 5 s, and the slow lifting rate was 0.5 μm / s;
[0061] The lithium tantalate bonding sheet was finely thinned, with a fine thinning removal amount of 10μm, a grinding wheel speed of 1300rpm, and a stage speed of 300rpm; the fine thinning was divided into 3 steps, the first step was a removal amount of 7μm, and a removal rate of 0.4μm / s; the second step was a removal amount of 2μm, and a removal rate of 0.2μm / s; the third step was a removal amount of 1μm, and a removal rate of 0.1μm / s; the slow lift time was 10s, and the slow lift rate was 0.2μm / s;
[0062] The spark time after thinning is 8s; the cleaning time after thinning is 10s, and the drying and purging time is 10s;
[0063] (2) Use a polishing correction wheel to dress the polishing pad, the correction wheel speed is 80 rpm, the correction wheel pressure is 1.5 psi, and the scanning time is 5 s;
[0064] (3) The bonded wafer to be polished is adsorbed onto the polishing head holding ring and pressed down onto the carrier;
[0065] (4) According to the film thickness distribution of the lithium tantalate bonding sheet after thinning, determine the reference pressure P of the reference area Zone 1 Wafer , and calculate the set pressure of Zone2 / Zone3 / Zone4 according to formula (1), pressurize the bond wafer to be polished step by step in different zones, and measure the film thickness waveform in real time, so as to adjust the pressurization formula based on the fitting model; the maximum pressure of the wafer is 4psi, the maximum pressure of the retaining ring is 4psi, the maximum speed of the polishing head is 75rpm, and the maximum speed of the polishing disc is 70rpm. The specific procedures are shown in Table 1:
[0066] Table 1 Polishing process parameters
[0067]
[0068] (5) The lithium tantalate bonding sheet after polishing was scrubbed for 120 seconds and dried for 120 seconds. The final measured film thickness of the lithium tantalate bonding sheet prepared in Example 1 is shown in Table 2 and Figure 3 As shown:
[0069] Table 2 Film thickness of lithium tantalate bonding sheet after polishing
[0070]
[0071] Example 2
[0072] (1) The lithium tantalate bonding wafer was rough thinned, with a rough thinning removal amount of 200 μm, a grinding wheel speed of 1800 rpm, and a stage speed of 300 rpm; the rough thinning was divided into two steps, the first step of the removal amount was 195 μm, and the removal rate was 1 μm / s; the second step of the removal amount was 5 μm, and the removal rate was 0.5 μm / s; the slow lifting time was 5 s, and the slow lifting rate was 0.5 μm / s;
[0073] The lithium tantalate bonding sheet was finely thinned, with a fine thinning removal amount of 10μm, a grinding wheel speed of 1300rpm, and a stage speed of 300rpm; the fine thinning was divided into 3 steps, the first step was a removal amount of 7μm, and a removal rate of 0.4μm / s; the second step was a removal amount of 2μm, and a removal rate of 0.2μm / s; the third step was a removal amount of 1μm, and a removal rate of 0.1μm / s; the slow lift time was 10s, and the slow lift rate was 0.2μm / s;
[0074] The spark time after thinning is 8s; the cleaning time after thinning is 10s, and the drying and purging time is 10s;
[0075] (2) Use a polishing correction wheel to dress the polishing pad, the correction wheel speed is 80 rpm, the correction wheel pressure is 1.5 psi, and the scanning time is 5 s;
[0076] (3) The bonded wafer to be polished is adsorbed onto the polishing head holding ring and pressed down onto the carrier;
[0077] (4) According to the film thickness distribution of the lithium tantalate bonding sheet after thinning, determine the reference pressure P of the reference area Zone 1 Wafer , and calculate the set pressure of Zone2 / Zone3 / Zone4 according to formula (1), pressurize the bond wafer to be polished step by step in different zones, and measure the film thickness waveform in real time, so as to adjust the pressurization formula based on the fitting model; the maximum pressure of the wafer is 4psi, the maximum pressure of the retaining ring is 4psi, the maximum speed of the polishing head is 75rpm, and the maximum speed of the polishing disk is 70rpm. The specific procedures are shown in Table 3:
[0078] Table 3 Polishing process parameters
[0079]
[0080] (5) Brush the polished lithium tantalate bonding wafer for 120 seconds and spin dry for 120 seconds.
[0081] The polishing pad, retaining ring and halogen lamp for film thickness measurement were divided into use stages with 1000min intervals. The polishing thickness and polishing time were recorded to calculate the polishing rate every 40s, and the polishing rate curve was fitted. Figure 4 It can be seen that, except when the polishing time is less than 20s, the polishing rate curve has large fluctuations due to the amount of data and polishing stability. The rest of the rate curves can be fitted. And because the relationship between the removal amount and the polishing time is not linear, the fitting is of great reference significance for mass production operations.
[0082] The lithium tantalate bonding sheet prepared in the embodiment of the present invention has been inspected to have no scratches or surface defects, and meets the subsequent device processing requirements.
[0083] Comparative Example
[0084] (1) The lithium tantalate bonding wafer was rough thinned, with a rough thinning removal amount of 200 μm, a grinding wheel speed of 1800 rpm, and a stage speed of 300 rpm; the rough thinning was divided into two steps, the first step of the removal amount was 195 μm, and the removal rate was 1 μm / s; the second step of the removal amount was 5 μm, and the removal rate was 0.5 μm / s; the slow lifting time was 5 s, and the slow lifting rate was 0.5 μm / s;
[0085] The lithium tantalate bonding sheet was finely thinned, with a fine thinning removal amount of 10μm, a grinding wheel speed of 1300rpm, and a stage speed of 300rpm; the fine thinning was divided into 3 steps, the first step was a removal amount of 7μm, and a removal rate of 0.4μm / s; the second step was a removal amount of 2μm, and a removal rate of 0.2μm / s; the third step was a removal amount of 1μm, and a removal rate of 0.1μm / s; the final slow lift time was 10s, and the slow lift rate was 0.2μm / s;
[0086] The spark time after thinning is 8s; the cleaning time after thinning is 10s, and the drying and purging time is 10s;
[0087] (2) Use a polishing correction wheel to dress the polishing pad, the correction wheel speed is 80 rpm, the correction wheel pressure is 1.5 psi, and the scanning time is 5 s;
[0088] (3) The bonded wafer to be polished is adsorbed onto the polishing head holding ring and pressed down onto the carrier;
[0089] (4) According to the film thickness of the thinned lithium tantalate bonded wafer, the film thickness waveform is measured in real time. The maximum pressure of the wafer is 4 psi, the maximum pressure of the retaining ring is 4 psi, the maximum speed of the polishing head is 75 rpm, and the maximum speed of the polishing disk is 70 rpm. The specific procedure is shown in Table 4 below:
[0090] Table 4 Polishing process parameters
[0091]
[0092] (5) The bonding sheet after brushing and polishing was washed for 120 seconds and dried for 120 seconds. The final measured film thickness of the lithium tantalate bonding sheet prepared in this comparative example is shown in Table 5 and Figure 5 As shown:
[0093] Table 5 Film thickness of lithium tantalate bonding sheet after polishing
[0094]
[0095] Comparing Table 2 and Table 5, Figure 3 and Figure 5 It can be seen that the range of the film thickness σ after polishing in Example 1 (73.963~152.464) is significantly smaller than the range of the film thickness σ after polishing in the comparative example (159.688~234.966), which proves that the technical solution of the present invention significantly improves the uniformity of the film thickness of the lithium tantalate bonding sheet and the process is stable.
[0096] The embodiments described in this specification are only exemplary embodiments for explaining the technical solution of the present invention and do not constitute a restrictive interpretation of the claims. For those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is limited by the attached claims and their equivalents.
Claims
1. A method for improving the uniformity of film thickness of a lithium tantalate bonding sheet, characterized in that: The following steps are involved: Step a: thinning the lithium tantalate bonding sheet, including: The lithium tantalate bonding sheet is subjected to a rough thinning process in sequence to reduce the thickness by a first removal amount; and Performing fine thinning processing on the lithium tantalate bonding sheet to reduce the second removal amount; Step b: pressurizing and polishing the bonding sheet according to the film thickness distribution of the thinned lithium tantalate bonding sheet, fitting the polishing rate model according to the film thickness measured in real time, and adjusting the pressurizing formula for polishing.
2. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step a, the first removal amount is greater than 50 μm, the grinding wheel used for rough thinning is 3000-4000 mesh, the grinding wheel speed is 1500-2000 rpm, the stage speed is 100-500 rpm, the slow lifting time is 5-10 s, and the slow lifting rate is 0.5-0.8 μm / s; Among them, the grinding wheel used for rough thinning is preferably 3000 mesh; The second removal amount is 10-15 μm, the grinding wheel used for fine thinning is 8000 mesh, the grinding wheel speed is 1000-1500 rpm, the stage speed is 100-300 rpm, the slow lifting time is 5-15 s, and the slow lifting rate is 0.1-0.5 μm / s; Among them, the fine thinning is divided into three steps. The first step has a removal amount of 7~12μm and a removal rate of 0.3~0.5μm / s; the second step has a removal amount of 2μm and a removal rate of 0.1~0.3μm / s; the third step has a removal amount of 1μm and a removal rate of 0.05~0.1μm / s.
3. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step a, after the lithium tantalate bonding sheet is thinned, the spark time is 5 to 10 seconds, and the spark time is positively correlated with the extreme difference in film thickness.
4. The method for improving the uniformity of film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step b, the maximum pressure of the wafer is ≤6psi, the maximum pressure of the retaining ring is ≤6psi, the maximum speed of the polishing head is ≤100rpm, and the maximum speed of the polishing disk is ≤100rpm, wherein the speed of the polishing head must be greater than the speed of the polishing disk, and the difference between the two is 3~5rpm.
5. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step b, during polishing, the polishing head swings left and right with an amplitude of 30 to 50 cm and a swing rate of 5 to 10 cm / min.
6. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step b, the bonding sheet is divided into a circular area and three adjacent concentric annular areas surrounding the circular area in sequence, the centers of the circular area and the concentric annular areas coincide with the center of the lithium tantalate bonding sheet, and the film thickness distribution of each area after thinning is measured by a film thickness meter.
7. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step b, the lithium tantalate bonding sheet is pressurized in zones and steps.
8. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 7, characterized in that: The zoned pressurization method in step b is: taking the outermost annular area of the lithium tantalate bonding sheet as the reference area, and determining the set pressure of the remaining areas according to the percentage of the average film thickness of the remaining areas being greater than or less than the average film thickness of the reference area, and pressurizing.
9. The method for improving the uniformity of film thickness of a lithium tantalate bonding sheet according to claim 7, characterized in that: The stepwise pressurization method in step b is as follows: the pressure increase or decrease in adjacent pressurization procedures does not exceed 1.5 psi.
10. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 7, characterized in that: When the pressure is applied step by step in step b, the wafer pressure and the retaining ring pressure must be adjusted to the maximum after the polishing head rotation speed and the stage rotation speed reach the maximum first.
11. The method for improving the uniformity of film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step b, the real-time film thickness measurement method is a spectral analysis measurement method. The refractive index of lithium tantalate is 2.
18. When the processed film thickness is greater than 5 μm, the measurement clutter at 2 μm needs to be filtered out.
12. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 1, characterized in that: In the step b, a polishing rate model is fitted at different stages of polishing for stop thickness compensation. Under the premise of consistent polishing procedures, the polishing pad, retaining ring and halogen lamp for film thickness measurement are divided into use stages with 1000 minutes as intervals. The polishing thickness and polishing time are recorded to calculate the polishing rate every 40 seconds, and the polishing rate curve is fitted to calculate whether the final stop thickness is reasonable and obtain compensation; then secondary polishing is performed.
13. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 12, characterized in that: The total effective polishing time of the polishing rate model is within 200 seconds.
14. The method for improving the uniformity of film thickness of a lithium tantalate bonding sheet according to claim 12, characterized in that: The secondary polishing includes flat polishing and zone-by-zone step-by-step pressurized polishing performed sequentially.
15. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 12, characterized in that: In the secondary polishing, the flat polishing time is 200s, and the zone-by-zone step-by-step pressurized polishing rate is 80% of the rate calculated by the primary polishing rate model.
16. The method for improving the uniformity of film thickness of a lithium tantalate bonding sheet according to claim 8, characterized in that: When the zone is pressurized, the calculation method of the set pressure of different zones is to determine the set pressure of the reference zone as the reference pressure P Wafer , according to the percentage of the average film thickness of the remaining areas greater than or less than the average film thickness of the reference area, calculate the set pressure of any area in the remaining areas: ; Among them, P i is the set pressure of any of the remaining areas, D i is the average film thickness of the region, i=2, 3, 4; D1 is the average film thickness of the reference region; When the range of the mean film thickness is less than 600nm, P Wafer =4psi, α =1.0; When the range of the mean film thickness is greater than or equal to 600nm and less than 1000nm, P Wafer =3psi, α =1.3; When the range of the mean film thickness is greater than or equal to 1000nm, P Wafer =3psi, α =1.
5.
17. The method for improving the uniformity of the film thickness of a lithium tantalate bonding sheet according to claim 16, characterized in that: In the remaining regions, there is at least one region where the calculated set pressure value is less than the reference pressure P Wafer When the actual set pressure of all zones increases by the same value on top of the original set pressure, the minimum value of the actual set pressure in the remaining zones is equal to the reference pressure P Wafer .
18. The method for improving the uniformity of film thickness of a lithium tantalate bonding sheet according to claim 16, characterized in that: When the calculated value of the set pressure is greater than 6 psi, 6 psi is used as the actual set pressure.
Citation Information
Patent Citations
Thin film arranged on substrate and preparation method of thin film
CN104779143A
Bonding wafer polishing method
CN118081603A
Processing end point detecting method, polishing method and polishing apparatus
CN102490112A
On-line plainness control system for copper CMP (Chemical Mechanical Planarization)
CN107214610A
Polishing equipment and polishing pressure control method and device thereof
CN107336126A
Cited By
Processing method of silicon carbide substrate
CN121360999A
Wafer film thickness uniformity correction method based on double chemical mechanical polishing devices
CN121928459A
A method for correcting wafer film thickness uniformity based on dual chemical mechanical polishing equipment
CN121928459B
Preparation process of secondary bonding lithium tantalate composite substrate and flexible lithium tantalate composite substrate
CN122294825A